2022
DOI: 10.1108/jocm-10-2021-0321
|View full text |Cite
|
Sign up to set email alerts
|

How does institutional environment in the digital context affect technology entrepreneurship? The moderating roles of government digitalization and gender

Abstract: PurposeBased on institutional theory, this study aims to analyze the influencing mechanisms of the institutional environment in the digital context on technology entrepreneurship.Design/methodology/approachUsing data from the Global Entrepreneurship Monitor, World Bank and World Economic Forum, this study builds a multilevel database covering 79 countries and 97,146 individuals from 2013 to 2017. A mixed-effects logistic regression model with the fixed part and random part was chosen to test the hypotheses in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 83 publications
0
10
0
1
Order By: Relevance
“…The main external reason is that digitisation has changed the process and form of technological entrepreneurship, thereby affecting knowledge creation, acquisition and re-creation (Fuller and Pickernell, 2018). Jiao et al (2022) revealed that different dimensions of the institutional environment in the digital context have varying impacts on individual technology entrepreneurship and that digital networks/internet and innovation culture positively impact technology entrepreneurship. The external environment stems from globalisation, supported by emerging information technologies, and places higher demand on digital-based enterprises to engage in collaborative innovation and learning (i.e.…”
Section: Understanding Digital Entrepreneurship Towards a Knowledge M...mentioning
confidence: 99%
“…The main external reason is that digitisation has changed the process and form of technological entrepreneurship, thereby affecting knowledge creation, acquisition and re-creation (Fuller and Pickernell, 2018). Jiao et al (2022) revealed that different dimensions of the institutional environment in the digital context have varying impacts on individual technology entrepreneurship and that digital networks/internet and innovation culture positively impact technology entrepreneurship. The external environment stems from globalisation, supported by emerging information technologies, and places higher demand on digital-based enterprises to engage in collaborative innovation and learning (i.e.…”
Section: Understanding Digital Entrepreneurship Towards a Knowledge M...mentioning
confidence: 99%
“…, 2022). Third, although the difficulty for individual entrepreneurs to implement significant investments (Jiao et al. , 2022), we discover how even in the case of the metaverse, support from public companies (e.g.…”
Section: Resultsmentioning
confidence: 94%
“…While digital pervasiveness is highest in large companies, this is more limited for small-to-medium-sized companies or single-entrepreneurship entities. For example, Jiao et al (2022) highlight how digital entrepreneurship is more difficult in single-entrepreneurship cases and is positively influenced by exposure to digital networks and innovative culture, even according to the gender of the entrepreneur himself. Other studies point out that being a digital entrepreneur depends on variables such as business innovativeness, intentionality, convenience, culture, flexible design, entrepreneurship orientation, generality, openness, network, and technology orientation (Dutot and van Horne, 2015;Upadhyay et al, 2022).…”
Section: Literature Review 21 Digital Entrepreneurshipmentioning
confidence: 99%
See 2 more Smart Citations